A New Bi-Level Encoding and Decoding Scheme for Pixel Expansion Based Visual Cryptography - Barik, Ram Chandra; Sahu, Sitanshu Sekhar; Changder, Suvamoy (International journal of rough sets and data analysis, 2019)
Mapping of image-based object textures to ASCII characters can be a new modification towards visual cryptography. Naor and Shamir proposed a new dimension of Information security as visual cryptography which is a secret sharing scheme among N number of participants with pixel expansion. Later on, many researchers extended the visual secret sharing scheme with no expansion of pixel regions in binary and color images. By stacking k shares the secret can be decoded using normal vision. In this paper the authors have proposed a modification towards visual cryptography by converting the message in the form of printable ASCII character-based numerical encoding patterns in a binary host image. The encoding of the message is represented as ASCII numeric and a texture of those numeric are arranged to form a binary host image. Then, N numbers of shares are built up but after stacking all the shares the decoding of the message is achieved by converting ASCII numeric to the secret.